Efficacy of Hongjing I granule, an herbal medicine, in patients with mild to moderate erectile dysfunction in a randomized controlled trial - Xu, Run-Nan; Guo, Jun; Zhang, Chun-He; Zhou, Qing; Gen, Qiang; Wang, Fu; Zhao, Yu; Luo, Xin-Yun; Li, Yan-Feng; Fu, Yi-Jia; Zhang, Xin; Wang, Wen-Zhi; et al. (Frontiers in Pharmacology, 2024)
In both primary outcomes, HJIG proved superior to the placebo. Additionally, improvements in TCM symptom scores were notably greater in the HJIG group relative to the placebo, with no adverse events reported across both groups.The Hongjing I granule significantly markedly improved outcomes symptoms forin patients with mild to moderate ED. However, to validate these findings, further extended randomized trials are warranted.The study has been registered in the Chinese Clinical Trial Registry (ChiCTR) and the registration number was ChiCTR2000041127.